Three pairs of luminescent coordination polymers based on CoII and CdII clusters for the detection of antibiotics, pesticides and chiral nitro aromatic compounds. Issue 16 (4th March 2020) - Zhang, Li-Qing; Wang, Xiu-Wen; Gu, Lei; Yu, Ying-Hui; Gao, Jin-Sheng
Abstract : Three pairs of luminescent coordination polymers based on ( R / S )-H2 cna and (1 R, 2 R /1 S, 2 S )-H3 cpba for the detection of antibiotics, pesticides and chiral nitro aromatic compounds. Abstract : Three couples of coordination polymers (CPs), namely, [Co(( R / S )-Hcna)2 ] n (1-D/L ), [Cd6 ((1 R, 2 R /1 S, 2 S )-cpba)4 (phen)6 (H2 O)3 ] n (2-D/L ) and [Cd2 ((1 R, 2 R /1 S, 2 S )-Hcpba)2 (phen)2 ] n (3-D/L ) {( R / S )-H2 cna = ( R / S )-6-(1-carboxyethoxy)-2-naphthoic acid, (1 R, 2 R /1 S, 2 S )-H3 cpba = (1 R, 2 R /1 S, 2 S )-2, 2′-((5-carboxy-1, 3-phenylene)bis(oxy))dipropionic acid, phen = 1, 10-phenanthroline} are successfully synthesized under hydrothermal conditions. Structural analysis shows that CP 1 has a 3D 3, 6-c net structure with a point symbol of (4·6 2 )2 (4 2 ·6 10 ·8 3 ). CPs 2 and 3 are obtained under very similar reaction conditions except using different solvent ratios. The presence of the planar chelating ligand phen in CPs 2 and 3 limited the spatial growth of the structure, resulting in the formation of different 1D structures. All CPs crystallized in the chiral space group P 21, CPs 1–3 are all SHG active. Their luminescence sensing activities for organics such as antibiotics, pesticides and nitro aromatics are also investigated. The results showed that CP 1 can effectively identify trace amounts of nitrofurans (NFs) and CP 3 has obvious recognition ability toward nitrofurans (NFs) and nitroimidazoles (NMs). Both CPs 1 and 3 could selectively detect 2, 6-dichloro-4-nitroaniline (DCN). The luminescence of CPs 1 and 3 can also be quenched by (D/L)-4-nitrophenylalanine ((D/L)-NPA) and (1 R, 2 R /1 S, 2 S )-2-amino-1-(4-nitrophenyl)propane-1, 3-diol ((1 R, 2 R /1 S, 2 S )-ANPO).